Strategic interest in Eastern Europe: Perspectives of great powers - Yang, Soo Siang (Malaysian Institute of Defence and Security (MiDAS), 2018)
The current geopolitical construct of Eastern Europe is undeniably a consequence of the Second World War. A new world order formed, taking over the old world hegemony. This paper highlights the present day interest of great powers in this region, particularly with respect to its economic and security construct. The review is presented in order to better appreciate the present day relevance of the East European region to the great powers. The end of the Cold War in 1991 had also reshaped the geopolitical construct of the region - opening up the region to global commerce and integration into the EU sphere of opportunities, hence subjecting the region to international exploitation. The extent of global powers’ economic and security interests in Eastern Europe and relevant issues of international concerns are reviewed in this paper.